2008
DOI: 10.1073/pnas.0708017105
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the mechanical properties of a virus by protein engineering

Abstract: In a previous study, we showed that the DNA molecule within a spherical virus (the minute virus of mice) plays an architectural role by anisotropically increasing the mechanical stiffness of the virus. A finite element model predicted that this mechanical reinforcement is a consequence of the interaction between crystallographically visible, short DNA patches and the inner capsid wall. We have now tested this model by using protein engineering. Selected amino acid side chains have been truncated to specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 51 publications
3
106
0
2
Order By: Relevance
“…À ce jour, outre les études concernant le VIH-1, des études d'imagerie par AFM ont été réalisées sur plusieurs types de virus comme les bactériophages [27], des parvovirus [28], ou des virus plus complexes, comme le HSV (virus de l'herpès simplex) [29]. Comme en cryo-EM, la résolution de cette méthode est telle qu'il est possible d'observer les protubérances des protéines de structure de certains virus non enveloppés qui sont en général à symétrie icosaédrique, et d'en déterminer leur nombre de triangulation ainsi que leurs axes de symétrie [30].…”
Section: Resultsunclassified
See 1 more Smart Citation
“…À ce jour, outre les études concernant le VIH-1, des études d'imagerie par AFM ont été réalisées sur plusieurs types de virus comme les bactériophages [27], des parvovirus [28], ou des virus plus complexes, comme le HSV (virus de l'herpès simplex) [29]. Comme en cryo-EM, la résolution de cette méthode est telle qu'il est possible d'observer les protubérances des protéines de structure de certains virus non enveloppés qui sont en général à symétrie icosaédrique, et d'en déterminer leur nombre de triangulation ainsi que leurs axes de symétrie [30].…”
Section: Resultsunclassified
“…Des expériences de nano-indentation AFM réalisées sur des bactériophages remplis d'ADN double brin de différentes longueurs ont ainsi permis de mettre en évidence l'existence d'une pression interne exercée par le génome sur la paroi de la capside [31] (voir aussi [33]). Par ailleurs, dans le cas du virus minute des souris (MVM), un virus à symétrie icosaédrique, des différences de raideur de la capside virale ont pu être mesurées selon le positionnement du virus sur une surface (sur une face, une arrête ou un sommet) et il a été possible de les relier aux points d'attache de l'ADN à l'intérieur de la capside [28]. L'AFM permet ainsi d'apporter des informations physiques quantitatives à l'échelle de la particule unique, et d'éclairer certaines propriétés biologiques au cours du cycle infectieux.…”
Section: Resultsunclassified
“…To summarize, in this article we have shown that desiccation provokes the ejection of DNA from both a parvovirus (MVM) and a bacteriophage (29), but the 2 capsids behave differently: Desiccated MVM virions or empty capsids do not suffer a significant collapse. In contrast, desiccated 29 particles suffer a drastic collapse.…”
Section: Applied Physical Sciencesmentioning
confidence: 99%
“…5 Lower). Although we have isolated the capillary forces effect on viruses, the many differences in intersubunit interactions and stiffness between the 29 and MVM capsids (24,28,29), and possible differences in the structural role of hydration as explained above, also play an important role in the observed effects of desiccation.…”
Section: Applied Physical Sciencesmentioning
confidence: 99%
See 1 more Smart Citation